Changing youth behaviour in South Africa - Nelisiwe Khuzwayo; Myra Taylor; Catherine Connolly (AOSIS, 2020)
Background: Youth behaviour in South Africa continues to be a public health concern. Primary prevention interventions remain a pre-requisite for promotion of improved social and health outcomes. Aim: The aim of the study was to assess the impact of a behavioural youth risk reduction intervention among grade 10 learners. Setting: The Study was conducted in KwaZulu-Natal high schools, at UMgungundlovu District Municipality. Methods: We conducted a cluster randomised controlled trial at 16 KwaZulu-Natal high schools where learners completed a self- administered questionnaire assessing youth risk behaviours. Schools were divided into two arms, intervention and a control arms. Results: The intervention reduced learners' reports of carrying of a weapon to school in the past 30 days, but did not significantly reduce other assessed risk behaviours. Although the intervention appeared more likely to reduce learners' risk behaviours when compared to the control group, such as carrying weapons, risky sexual behaviour and alcohol and drug abuse. Conclusion: This study was unable to show statistical significance for these outcomes.